Pengolahan Limbah Gawai Menjadi Produk Dengan Nilai Sentimental Dalam Pendirian Usaha Rintisan Bingkai Jadoel Project - Pradnya Ananda, I Made Mardawa; Swandi, I Wayan; Bagus udayana, Anak Agung Gde (Program Studi Desain Komunikasi Visual, 2024)
With the rapid development and innovation in the world of Indonesian gadgets, manufacturers are starting to present a selection of cheap gadgets with modern specifications that can easily attract consumers' attention in Indonesia. However, this is often a reason for consumers to replace their devices when the latest variant is released to the public, either because they feel bored or the device they are using is old/outdated, or because the cheap price means the device cannot last long. This creates quite a serious problem because only a small portion of old gadgets can be reused and most of these gadgets end up as waste which can be dangerous to health because of the chemicals contained in the waste gadgets. However, the problem of gadget waste also presents several business opportunities, especially for those who pursue business in the creative industry. One form of product produced from processing this waste is the Teardown Frame. How this type of product can become a business opportunity in building a start-up business is the main priority of this research, a qualitative approach method is used to collect the necessary data and information, through Observation, Literature, Interviews, and Participants which helps the author in determining what business model is appropriate for this business as well as the production flow of the Teardown Frame product. Through this approach method, it can be concluded that this type of business has a fairly narrow market segment with a focus on the group/community of old-school goods enthusiasts as the main market segment, where the main quality offered is the nostalgic feeling of the product.